Implementasi dan Pemanfaatan Komunikasi Digital dalam Program Desa Berdaya oleh CSR PT. PLN Corporate University - Alkayla Karuni; Vivien Febri Astuti (Journal of Creative Student Research, 2026)
The success of PT PLN Corporate University’s Corporate Social Responsibility (CSR) initiative through the Desa Berdaya Program reflects the company’s strategic role in designing, managing, and communicating sustainable community empowerment programs. This study aims to examine the implementation of the Desa Berdaya Program and the use of social media by PT PLN Corporate University’s CSR initiative, which received the CSR Nusantara Awards 2025. This research employs a descriptive qualitative method to describe the program implementation process, the empowerment approach, and the application of digital communication support. The findings indicate that PT PLN Corporate University implemented its CSR program systematically through community asset identification, local potential mapping, integration of individual, group, institutional, and environmental assets, and active community participation. The program was also supported by the formulation of milestones, evaluation, and continuous monitoring as part of a measurable management mechanism. The Asset-Based Community Development (ABCD) approach is reflected in literacy strengthening, skills training, entrepreneurship development, circular economy practices, and the enhancement of added value in local commodities. The findings further reveal that program sustainability is determined not only by corporate support, but also by the community’s capacity to independently manage and develop local potential. In addition, the use of media relations and social media contributes to expanding public exposure, strengthening corporate image, and reinforcing the social legitimacy of the program. However, the implementation of digital communication still faces limitations, particularly in the consistency of disseminating program-related information. Therefore, social media management needs to be further optimized to support social documentation, community participation, and the continuous circulation of field-based information.